Pemantapan Etika Penelitian dan Integritas Akademis Mahasiswa Teknik Industri - Firdaus, M.; Sari, Resy Kumala (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
This community engagement activity aims to enhance students' understanding and readiness to apply research ethics. Prior to the training, the majority of participants had a good understanding; however, after the training, a significant improvement was observed, with over 70% of participants feeling more prepared to implement ethical values in their research. Evaluation of practical tasks from 48 participants indicated a positive overview, despite weaknesses in writing format and argument variation. Results from interviews and focus group discussions illustrated positive changes in participants' understanding and attitudes towards research ethics. The participant satisfaction survey reflected a high level of satisfaction (90%), while participants' recommendations supported the expansion of similar activities in the future. Overall, this training successfully increased awareness and implementation of research ethics among Industrial Engineering students.